GETTING OUT FROM REPEATED DOMESTIC VIOLENCE: EXPRESSION OF RESILIENCE - Siregar, Wahidah Zein Br (Kafa`ah: Journal of Gender Studies, 2024)
In general, it is not easy for women to quickly get out from domestic violence. There are many reasons for this: afraid of being stigmatized, uncertain toward the future lives, scare of their husbands, do not have families or friends to protect them, lack of income, do not have places to go if they should leave home, or believing that the violence is usual in a family life. This paper aims to tell stories of four Indonesian women who made decision to be free from repeated domestic violence that they got from their husbands. What are their stories? What kind of domestic violence did they get? How did they face the violence? What did they do to get out from the violence? Applying life story method, this research found that they got physical, psychological, and economic violence. They decide to get out from the domestic violence they face. For that, they get help from families, friends, neighbours, or centre for integrated service. They share an important point through their stories. Through the experience they got from the violence up to be able to be free from the violence, they express a resilience.